Interperiod Tax Allocation, Earnings Expectations, and the Behavior of Security Prices. - Beaver, William H.; Dukes, Roland E. (The Accounting Review, 1972)
This article presents information on some preliminary findings regarding the observed association between security prices and alternative income numbers, where the primary focus is upon the issue of interperiod tax allocation. The interperiod tax allocation controversy is an attractive research topic for several reasons. It is virtually impossible to resolve the controversy with traditional sorts of arguments. This is also true of many other measurement controversies in accounting and it is particularly obvious here. The controversy affects a large number of firms. Many other controversies tend to be of concern in only a few industries, while most firms have a deferred tax account. Although deferral is required, nondeferral income can be easily estimated from the financial statements. The association between the alternative earnings numbers and the behavior of security prices will indicate which method the market perceives to be the most related to the information used in setting equilibrium prices.